2009
DOI: 10.1002/jrs.2350
|View full text |Cite
|
Sign up to set email alerts
|

A study on red lead degradation in a medieval manuscriptLorvão Apocalypse(1189)

Abstract: The mechanisms of red lead degradation were studied in a medieval Portuguese codex, Lorvão Apocalypse (1189), by Raman microscopy (µ-Raman) and micro-X-ray diffraction (µ-XRD). The range of pigments found for the illuminations is mainly limited to vermilion, orpiment and red lead. Micro-Fourier transform infrared spectroscopy (µ-FTIR) determined that the pigments were applied in a proteinaceous binding medium. In the red and orange colours, arsenic (As) was determined, by micro-energy dispersive X-ray fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 31 publications
3
61
0
2
Order By: Relevance
“…This was known to artists and artisans, as demonstrated by the presence of a blank space between yellow orpiment and red lead in a 12th century illuminated manuscript, although mixtures of the two pigments do not behave consistently. The reaction between red lead and orpiment produced galena, which could further degrade into sulphates, and lead arsenate species [241]. Mimetite Pb 5 (AsO 4 ) 3 Cl was as well identified as a reaction product of minium and orpiment [186].…”
Section: Red Lead (Pb 3 O 4 )mentioning
confidence: 98%
See 1 more Smart Citation
“…This was known to artists and artisans, as demonstrated by the presence of a blank space between yellow orpiment and red lead in a 12th century illuminated manuscript, although mixtures of the two pigments do not behave consistently. The reaction between red lead and orpiment produced galena, which could further degrade into sulphates, and lead arsenate species [241]. Mimetite Pb 5 (AsO 4 ) 3 Cl was as well identified as a reaction product of minium and orpiment [186].…”
Section: Red Lead (Pb 3 O 4 )mentioning
confidence: 98%
“…It is soluble in diluted acids (nitric, chloridric, oxalic, acetic), with formation of the corresponding salts, and when heated it transforms to litharge [1,240]. It is sensitive to sulphur containing compounds, as H 2 S and SO 2 of atmospheric or biological origin, and pigments such as arsenic sulphides (As x S y ), vermillion (HgS) and ultramarine (Na 8 [Al 6 Si 6 O 24 ]S n ), especially in manuscripts, wall paintings, and in case the pigment is not mixed with a binder, which cause the formation of dark grey PbS [1,60,93,124,238,241] and of whitish PbSO 4 [59,68,233,242]. This was known to artists and artisans, as demonstrated by the presence of a blank space between yellow orpiment and red lead in a 12th century illuminated manuscript, although mixtures of the two pigments do not behave consistently.…”
Section: Red Lead (Pb 3 O 4 )mentioning
confidence: 99%
“…Over the past 10 years, we have contributed to the development of advanced techniques that allow us to characterize and rigorously quantify colour and colour loss in monastic manuscripts from the twelfth and thirteenth centuries [1][2][3][4]. More recently, these studies have also included books of hours as well as other artworks covering a period from the twelfth to the nineteenth centuries [5][6][7][8].…”
Section: Introduction (A) the Art Of Colour In Medieval Illuminationsmentioning
confidence: 99%
“…The matte look of gold powder, observed in elements 5 Galena was identified by Miguel et al [30] as a result of the reaction of orange of minium with orpiment (As 2 O 3 ) found in twelfth century Portuguese manuscripts.…”
Section: Migration Of Other Pigmentsmentioning
confidence: 91%
“…16d). As an hypothesis for the phenomenon, we proposed the reaction that involves the minium (Pb 3 O 4 ) and hydrogen sulphide in air (H 2 S) producing lead sulphide (II), called galena (PbS) 5 [30], of similar appearance to that of silver sulphide (Ag 2 S). In addition, some studies about this pigment and its degradation raise the hypothesis of the influence of humidity and binders in colour stability, relating its discolouration to an egg white tempera, probably due to the presence of sulfur [31][32][33].…”
Section: Oxidationmentioning
confidence: 99%